ANALISIS KOMPENSASI DALAM STRATEGI RETENSI PEKERJA LOKAL DI UD BERSAMA ELETRONIK - Emanuel Gea; Delipiter Lase; Eliagus Telaumbanua; Robin Markus Putra Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the compensation system as part of the employee retention strategy for local workers at UD Bersama Elektronik. Human resources are a crucial asset for companies, especially local workers who possess a strong understanding of local social and market conditions. However, an inadequate compensation system may lead to job dissatisfaction and increased employee turnover. Therefore, this research focuses on how financial and non-financial compensation is implemented and its role in retaining local workers. This research employs a qualitative approach with a descriptive research design. Data were collected through observations, in-depth interviews with management and local employees, and documentation related to human resource policies at UD Bersama Elektronik. The data analysis techniques consisted of data collection, data reduction, data presentation, and conclusion drawing and verification. The results indicate that the compensation system at UD Bersama Elektronik includes direct financial compensation such as basic salary, allowances, incentives, and bonuses, as well as non-financial compensation in the form of work facilities and a supportive work environment. Compensation determination is based on job position, responsibilities, length of service, and employee performance. Although the compensation provided is considered competitive at the local level, several challenges remain, including the company’s financial limitations and the lack of an optimal performance-based compensation system. Employee retention strategies can be strengthened through improvements in a more fair, structured, and sustainable compensation system to enhance job satisfaction and employee loyalty.